2017
DOI: 10.1017/s0950268817001479
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation and co-infections of all dengue virus serotypes in Hyderabad, India 2014

Abstract: The burden of dengue virus infections increased globally during recent years. Though India is considered as dengue hyper-endemic country, limited data are available on disease epidemiology. The present study includes molecular characterization of dengue virus strains occurred in Hyderabad, India, during the year 2014. A total of 120 febrile cases were recruited for this study, which includes only children and 41 were serologically confirmed for dengue positive infections using non-structural (NS1) and/or IgG/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Co-infection with multiple serotypes poses risk of emergence of recombinant virus strains that could have distinct properties. Co-circulation of all the four serotypes in a single outbreak has been reported earlier with 42.9% and 45.4% cases of co-infection in Karnataka and Hyderabad respectively [ 28 , 52 ]. Significant co-infection (15% -43%) has been reported from northern [ 24 , 26 ], and eastern India[ 25 ] without detecting all the 4 serotypes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Co-infection with multiple serotypes poses risk of emergence of recombinant virus strains that could have distinct properties. Co-circulation of all the four serotypes in a single outbreak has been reported earlier with 42.9% and 45.4% cases of co-infection in Karnataka and Hyderabad respectively [ 28 , 52 ]. Significant co-infection (15% -43%) has been reported from northern [ 24 , 26 ], and eastern India[ 25 ] without detecting all the 4 serotypes.…”
Section: Discussionmentioning
confidence: 93%
“…Significant co-infection (15% -43%) has been reported from northern [ 24 , 26 ], and eastern India[ 25 ] without detecting all the 4 serotypes. These regions with circulation of more than one serotype simultaneously are of high significance as they are more prone to severe dengue infection [ 28 , 52 ]. However, we did not find evidence of co-infection among the patients studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings showed that subsequent infection with a different serotype may lead to increased disease severity because antibodies against the previous serotype do not cross-neutralize the subsequent heterologous invading serotype, but induce antibody-dependent enhancement that increases replication inside target Fc receptor-bearing cells [33,34]. Co-infection with multiple DENV serotypes may increase the risk of emergence of recombinant strains that have different characteristics and the areas with a circulation of more than one serotype have been classified as more prone to severe DENV infections [31,35]. Co-circulation of dengue virus serotypes and occurrence of serotypes co-infection in Tanzania provide alert on the possibility of an increased risk of severe dengue in the country.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that a subsequent infection with a second serotype can 309 produce more severe symptoms (15). This situation becomes challenging when multiple 310 serotypes co-circulate (16). Mosquitoes co-infected with different DENV serotypes are 311 occasionally detected (17).…”
mentioning
confidence: 99%